The Lollipop with Lemon Aroma May Be Promising in Nausea and Vomiting in Pregnancy - Ismail Biyik; Fatih Keskin (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: To determine the effect of lemon-flavored lollipop on nausea and vomiting of pregnancy.